2002
DOI: 10.1124/mol.62.6.1506
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of G Protein-Coupled Receptor Kinase 2 Expression in U-937 Cells Attenuates H2 Histamine Receptor Desensitization and Induces Cell Maturation

Abstract: Histamine and H2 agonists transiently induce an important cAMP response in promonocytic U-937 cells but fail to induce monocytic differentiation because of a rapid receptor desensitization mediated by G protein-coupled receptor kinases (GRKs). The aims of the present study were to investigate the participation of GRK2 in the desensitization mechanism of the H2 receptor in U-937 cells by reducing GRK2 levels through antisense technology and to evaluate the differentiating capacity of cells expressing lower GRK2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 30 publications
2
28
1
Order By: Relevance
“…On the contrary, GRKs seem to be involved in this process, considering that in a stable U937 clone with reduced GRK2 expression (Fernandez et al, 2002) the rate of recovery of CysLT 1 functionality was faster than that in control U937 cells, and a GRK2 inhibitor partially reduced agonist-induced desensitization. However, a 30 minute pretreatment with GFX was able to increase LTD 4 -induced [Ca 2+ ] i levels (data not shown), suggesting a 'tonic' desensitization of the CysLT 1 receptor by PKC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, GRKs seem to be involved in this process, considering that in a stable U937 clone with reduced GRK2 expression (Fernandez et al, 2002) the rate of recovery of CysLT 1 functionality was faster than that in control U937 cells, and a GRK2 inhibitor partially reduced agonist-induced desensitization. However, a 30 minute pretreatment with GFX was able to increase LTD 4 -induced [Ca 2+ ] i levels (data not shown), suggesting a 'tonic' desensitization of the CysLT 1 receptor by PKC.…”
Section: Discussionmentioning
confidence: 99%
“…5B shows that CysLT 1 receptor functionality is recovered faster in a stable U937 clone (D5 clone) with reduced GRK2 expression (Fernandez et al, 2002) than in control dU937 cells after agonistinduced homologous desensitization. In addition, a 30 minute pre-treatment with 1 M of the GRK2 inhibitor (Iino et al, 2002) decreased CysLT 1 homologous desensitization to 78% (data not shown) compared with control cells (>90%, see Fig.…”
Section: Effect Of Cysltmentioning
confidence: 99%
“…Because this experimental procedure may eventually modify the stoichiometry among the components of the signaling pathway and ultimately have an impact on the cellular response, we evaluated the role of arrestin and dynamin in H2r internalization in U937 cells. In this leukemic cell line, we reported previously moderate expression of H2r and its coupling to the Gs pathway, its desensitization mechanism, and its participation in cell maturation (Lemos Legnazzi et al, 2000;Ferná ndez et al, 2002). U937 cells were stably transfected with ␤-arrestin (319-418) or dynaminK44A.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the wide therapeutic use of H2 ligands for gastric ulcers, their cardioprotective effects in patients with chronic heart failure Kim et al, 2006), and their implication in HL-60 and U937 leukemic cell maturation (Tasaka et al, 1994;Ferná ndez et al, 2002), little is known about H2r regulation. H2r internalization was first reported in human embryonic kidney 293 cells in which the authors showed that histamine treatment induces loss of H2r membrane immunoreactivity (Smit et al, 1995).…”
Section: Abbreviationsmentioning
confidence: 99%
“…Cells were transfected as reported previously (Ferná ndez et al, 2002). Briefly, cells were harvested by centrifugation from cultures in exponential growth phase, washed once in phosphate-buffered saline, and resuspended at 10 6 cells/ml in fresh RPMI 1640 medium on ice.…”
Section: Stable Transfection Of U-937 Cellsmentioning
confidence: 99%